Painful conditions in the achilles tendon region in elite badminton players - Fahlstrom, M.; Lorentzon, R.; Alfredson, H. (2002)
The purpose of this study was to investigate the prevalence and characteristics of painful conditions in the Achilles tendon region in elite badminton players. The study group consisted of 66 players in the Swedish elite division (highest level) in badminton, 41 men (mean age, 24.4 years) and 25 women (mean age, 21.9 years). Twenty-one players (32%) reported the occurrence of a disabling painful condition in the Achilles tendon region during the previous 5 years, and 11 players (17%) had an ongoing painful condition. A majority of the painful conditions (12 of 21, or 57%) were described as involving the midportion of the Achilles tendon. The players who had a painful condition reported a significantly higher weekly training load as measured by the number of hours spent in total training, badminton training, and endurance and strength training. There were no differences in age, sex, and body mass index between the players with and without painful conditions in the Achilles tendon region. Am J Sports Med 2002 Jan-Feb;30(1):51-4